PERANCANGAN KONSEPTUAL MEDIA PEMBELAJARAN IPS TERPADU BERBASIS DIGITAL BERMUATAN TRADISI MAPPOGAU SIHANUA PADA MASYARAKAT ADAT KARAMPUANG UNTUK SMP DI KABUPATEN SINJAI - Alifa Nur Anugrah; Elim Dian Masero; Hasni; Ahmad Syawaluddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to design a digital-based integrated social studies learning media concept that incorporates the Mappogau Sihanua tradition in the Karampuang indigenous community in Sinjai Regency. The research method used is a Systematic Literature Review (SLR) by analyzing 12 open access publications related to digital learning media, integrated social studies learning, and local wisdom-based education. The results of the study indicate that digital media such as e-modules, interactive videos, educational games, digital student worksheets, learning multimedia, and culture-based quiz applications can increase student learning motivation, strengthen interactions between teachers and students, and make learning more interesting and contextual. On the other hand, the Mappogau Sihanua tradition contains values ​​of togetherness, mutual cooperation, religiosity, morality, and social responsibility that are relevant for character education. The integration of these values ​​in digital learning media is also in line with UNESCO recommendations regarding the importance of local knowledge-based education for social sustainability. Thus, the conceptual design of digital-based social studies learning media containing the Mappogau Sihanua tradition can be a learning innovation for junior high schools in Sinjai Regency while supporting the preservation of local cultural identity.